2006
DOI: 10.1080/13880200600714111
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Alkaloids fromPseuduvaria setosa.

Abstract: Two dioxoaporphine alkaloids, N-methylouregidione (1) and ouregidione (2), and two oxoaporphine alkaloids, liriodenine (3) and oxostephanine (4), were isolated from the aerial part of Pseuduvaria setosa (King) J. Sinclair. All four alkaloids displayed antituberculosis activity against Mycobacterium tuberculosis, with 3 as the most active at minimum inhibitory concentration (MIC) of 12.5 mg=ml. Compound 3 was also the only alkaloid isolated from this plant that displayed antimalarial activity against Plasmodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…In the present study, we examined the antiproliferative activity of the other two alkaloids isolated from leaves and twigs of P. rugosa, 1,2,3-trimethoxy-5-oxonoraporphine and ouregidione, on human leukemic cell lines. Previous reports showed that ouregidione exhibited larvicidal activity against the mosquito Aedes aegypti (Ee et al, 1999), cytotoxic activities against human breast cancer (BC) and human small lung cancer (NCI-H187) (Wirassathien & Boonarkart, 2006), together with cytotoxicity towards DNA repair-deficient strains, RAD 52Y and RS 321 (Wijeratne et al, 1996). The results of the MTT reduction assay found that 1,2,3-trimethoxy-5-oxonoraporphine and ouregidione induced cytotoxicity of HL-60, U937 and K562 cells in a dose-dependent manner whereas 1,2,3-trimethoxy-5-oxonoraporphine is more active than ouregidione.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we examined the antiproliferative activity of the other two alkaloids isolated from leaves and twigs of P. rugosa, 1,2,3-trimethoxy-5-oxonoraporphine and ouregidione, on human leukemic cell lines. Previous reports showed that ouregidione exhibited larvicidal activity against the mosquito Aedes aegypti (Ee et al, 1999), cytotoxic activities against human breast cancer (BC) and human small lung cancer (NCI-H187) (Wirassathien & Boonarkart, 2006), together with cytotoxicity towards DNA repair-deficient strains, RAD 52Y and RS 321 (Wijeratne et al, 1996). The results of the MTT reduction assay found that 1,2,3-trimethoxy-5-oxonoraporphine and ouregidione induced cytotoxicity of HL-60, U937 and K562 cells in a dose-dependent manner whereas 1,2,3-trimethoxy-5-oxonoraporphine is more active than ouregidione.…”
Section: Discussionmentioning
confidence: 99%
“…Biological activities of the four oxoaporphine alkaloids, N-methylouregidione, ouregidione, liriodenine and oxostephanine, isolated from the aerial part of Pseuduvariasetosashowed in vitroantituberculosis activity against Mycobacterium tuberculosis with MIC values of 100, 12.5 and 25 g/ml, respectively [16]. These results have demonstrated that aporphine alkaloids can be developed as potential anti-tubercular agents in chemotherapy [17].…”
Section: Pseuduvariasetosamentioning
confidence: 72%
“…The antimalarial activity of these compounds has been previously reported against P. falciparum Dd2 strain for the Flindersia alkaloids [5], against D6 and W2 strains for xylopine and voacamine [12,13] and against K1 strain for liriodenine [14]. However, as the activity can vary against P. falciparum strains with differing drug resistance profiles, in this study the antimalarial activity of the isolated compounds was assessed against a panel of both drug-sensitive (3D7) and drug-resistant (FCR3, HB3 and K1) strains (Table 1).…”
Section: Resultsmentioning
confidence: 95%